2015
DOI: 10.3892/mmr.2015.3993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH agonists on the expression of developmental follicular anti-mullerian hormone in varying follicular stages in cyclic mice in vivo

Abstract: Gonadotrophin-releasing hormone (GnRH) agonists (GnRHa) have been widely used to induce a state of downregulation for in vitro fertilization, and its direct effects on the pituitary are well known. However, the effects of GnRHa on the expression of anti-mullerian hormone (AMH) by follicles in varying stages in vivo remain to be fully elucidated. In the present study 84 cyclic mice were randomly divided equally into four GnRHa groups and three cyclic mice were used as a control group. The expression levels of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Increased oocyte yield, however, is more likely to be associated with the size of selectable follicle cohort. In cyclic mice, immunochemistry assay revealed that AMH expression of individual follicle initially increased and then decreased gradually during GnRH agonist treatment up to 7 days [11], but the late preantral follicle count increased significantly following 8-day downregulation with pharmacological dose (25 μg/day) of GnRH agonist injection [12]. These data may partially support the positive effect of GnRH agonist on the size of selectable follicle rather than per-follicle expression.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Increased oocyte yield, however, is more likely to be associated with the size of selectable follicle cohort. In cyclic mice, immunochemistry assay revealed that AMH expression of individual follicle initially increased and then decreased gradually during GnRH agonist treatment up to 7 days [11], but the late preantral follicle count increased significantly following 8-day downregulation with pharmacological dose (25 μg/day) of GnRH agonist injection [12]. These data may partially support the positive effect of GnRH agonist on the size of selectable follicle rather than per-follicle expression.…”
Section: Discussionmentioning
confidence: 79%
“…The dual effect of GnRH agonist on AMH observed in rodent may also explain the observation of Su et al that the change in AMH transferred from decrease to increase after GnRH agonist treatment [5]. The initial decrease may be due to suppression of per-follicle expression [11] and the following increase may reflect the changes in size of selectable follicle [12]. These data may imply that the timing of AMH measurement is associated with the direction of observed change in AMH levels following GnRH agonist treatment.…”
Section: Discussionmentioning
confidence: 80%
“…The true ovarian reserve is given by the number of primordial follicles left in the ovaries, and as the number of antral follicles that produce AMH correlates well with the number of primordial follicles, the hormone level can be used as a surrogate marker for the true ovarian reserve . However, the biomarker cannot be used as a surrogate marker for the ovarian reserve in certain situations; in women with hypothalamic amenorrhea either normal or elevated AMH levels have been described and in contrast, AMH is decreased in current users of oral contraceptives , and during long‐term treatment with GnRH agonists . Being aware of the different hormonal values in these groups is essential to avoid false conclusions from the AMH levels.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of changes in serum AMH levels may be related to the continued development of small follicles, which have the potential to grow independently of cyclic changes. Therefore, AMH can be a valuable and intuitive indicator (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%